Temporal and spatial dynamics of Tomato spotted wilt virus and its vector in a potato crop in Argentina - Salvalaggio, Andrea Eugenia (2017)
The nature of spatial and temporal dynamics of Tomato spotted wilt virus (TSWV) and its vector in a potato crop cv. Innovator without insecticide application is analysed. Seed tuber was analysed for the presence of TSWV as a source of initial inoculum. The presence of plants with symptoms of TSWV was evaluated by visual observation and DAS-ELISA analysis to confirm the virus infection. Thrips species were collected from leaves and inflorescences and identified under stereomicroscope. The distribution of symptomatic plants and thrips species was recorded five times at 14 days intervals. The initial seed tuber infection was of 1.1%. Disease incidence was 0% at 29 days after planting (DAP), 0.2% at 43 DAP, 2.2% at 56 DAP, 11.6% at 70 DAP and 14.6% at 84 DAP. The progress of the disease was adequately described by a Logistic model [y=0.15/(1+1205372.93 × exp (−0.22 × DAP))]. Thrips vector species identified as resident in the crop during the whole cycle were Thrips tabaci (n=423), Frankliniella occidentalis (n=141) and as occasional species, F. schultzei (n=34) and F. gemina (n=5) were found. At 43 and 56 DAP a random distribution pattern was observed and the thrips species found were T. tabaci (n=188) and F. occidentalis (n=105). An aggregated pattern was determined at 70 and 84 DAP. Spatial patterns of the disease spread suggest a polycyclic epidemic with TSWV secondary spread in the potato crop. Multiple control measures were deduced from these epidemiological results like virus testing in tubers, removal of external virus infection sources and thrips control.